Perbandingan Tingkat Kebugaran Jasmani Siswa Sekolah Menengah Atas Daerah Pegunungan Dan Daerah Rawa: The Comparison of Physical Fitness Levels of High School Students in Mountainous and Swampy Areas - Amalia, Bonita; Maulana, Ahmad; Ardinnata, Muhammad Yudhi (Universitas Hamzanwadi, 2025)
This study aims to determine the comparison of the level of physical fitness of high school students in mountainous areas and swamp areas. The population in this study were students of SMA Negeri Salam Babaris and SMA Negeri Candi Laras Selatan. researchers used purposive sampling technique. XI grade students of SMAN Salam Babaris as a mountainous area amounted to 74 students and XI grade students of SMAN Candi Laras Selatan as a swamp area amounted to 59 people. The data analysis technique used in this research is quantitative. From the above work results obtained T count = 0.05 and T table at a significant level of 5% with 1.97. Thus the price of T count = 0.05 is smaller than the price of T table = 1.97, so the null hypothesis is accepted and the alternative hypothesis is rejected. Based on facts like this, it can be concluded that means the difference in calculations is not significant. Based on the results of data analysis, hypothesis testing and discussion that have been presented, the researchers can conclude that in the research that has been conducted on high school students in mountainous areas and swamp areas, namely SMAN 1 Salam Babaris and SMAN 1 Candi Laras Selatan, the results show that there is no comparison of the level of physical fitness of high school students in mountainous areas and swamp areas, namely SMAN 1 Salam Babaris and SMAN 1 Candi Laras Selatan because the results of hypothesis testing show that T count (0.05) < T table (1.97).